2019
DOI: 10.1021/acs.chemmater.9b02141
|View full text |Cite
|
Sign up to set email alerts
|

Combined Theoretical and Experimental Investigations of Atomic Doping To Enhance Photon Absorption and Carrier Transport of LaFeO3 Photocathodes

Abstract: Perovskite-type lanthanum iron oxide, LaFeO3, is a p-type semiconductor that can achieve overall water splitting using visible light while maintaining photostability. These features make LaFeO3 a promising photocathode candidate for various photoelectrochemical cells. Currently, the photoelectrochemical performance of a LaFeO3 photocathode is mainly limited by considerable bulk electron–hole recombination. This study reports a combined theoretical and experimental investigation on the atomic doping of LaFeO3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…11 Celorrio et al reported photovoltages as high as 1.2 V vs. RHE for the hydrogen evolution reaction at LaFeO 3 (LFO). 12 Other studies involving LaFeO 3 [13][14][15][16][17] and YFeO 3 18 have also observed high photovoltages but EQE less than 1%. The origin of carrier losses remains to be fully elucidated.…”
mentioning
confidence: 95%
“…11 Celorrio et al reported photovoltages as high as 1.2 V vs. RHE for the hydrogen evolution reaction at LaFeO 3 (LFO). 12 Other studies involving LaFeO 3 [13][14][15][16][17] and YFeO 3 18 have also observed high photovoltages but EQE less than 1%. The origin of carrier losses remains to be fully elucidated.…”
mentioning
confidence: 95%
“…[ 9 ] Other ferrite photoanodes include ZnFe 2 O 4 , MgFe 2 O 4 , and CuFe 2 O 4 , achieving external quantum efficiency values of close to 10% and photocurrent onset potentials ranging from 0.6 up to 1 V. [ 10,11 ] Ferrite photocathodes such as LaFeO 3 and YFeO 3 have shown very interesting photovoltages for the hydrogen evolution reaction, but their activity is limited by bulk and surface recombination losses. [ 12–17 ] Ferroelectric materials such as BiFeO 3 and Bi 2 FeCrO 6 show complex PEC properties that have been linked to ferroelectric domains. [ 18,19 ] For instance, BiFeO 3 exhibits both n‐ and p‐type conductivity, including above photovoltages larger than the bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…33 In a more recent work, the same author demonstrated that with K doping, LFO photocathodes of high porosity were able to achieve À268 mA cm À2 at +0.6 V RHE , when compared with À124 mA cm À2 for pristine LFO in O 2 purged electrolyte. 34 LFO lms prepared by pulsed laser deposition (PLD) exhibited photocurrent values of À65 mA cm À2 at 0 V RHE under simulated sunlight (100 mW cm À2 ) in oxygen-containing electrolyte solutions. 35 LFO lms deposited by spray pyrolysis demonstrated a photocurrent density of À160 mA cm À2 at +0.26 V RHE under simulated sunlight (100 mW cm À2 ) and O 2 containing solution.…”
Section: Introductionmentioning
confidence: 99%